Air pollution monitoring system in semi enclosed building for agricultural sector - S., Nurulain; M S, Najib; E., Lewis; M R, Salim; H., Manap (IOP Publishing, 2020)
This article explains about the development of an optical sensor system to detect and measure ammonia emission in the agricultural field. At initial stage, an open path optical technique where a cylindrical chamber is used to detect low concentration of ammonia in the UV region. The methodology describing the working principle of the sensor and the wavelengths combination technique to enhance the Lower Detection Limit of the measurement. The result demonstrates that the developed optical sensor is able to measure ammonia concentration at around 212 nm. It also shows that by combining intensities at 2 adjacent wavelengths, the Lower Detection Limit has been improved to 2.25 ppm and 1 s response time is retained. Then the system is tested to monitor ammonia pollution in the cattle barn in Tipperary, Ireland. It shows that the developed system is able to detect and measure very low ammonia concentration which is below 2 ppm.